STRUCTURE OF A SAMPLE TRAINING COURSE AND MODERN REQUIREMENTS FOR IT - Ergashevich , Ernazarov Alisher (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
the structure of training, elements of training, type of training, type of training, teaching methodology, modern requirements for training are mentioned.